Access of People with Disabilities to Justice in Indonesia General Court System - Panggabean, Siska Naomi (The Center for Disability Studies and Services Brawijaya University, 2019)
Accessibility of people with disabilities is the main problem of this research. Focusing on justice and legal protection rights as one of the listed rights of people with disabilities in Law Number 8 of 2016, and its implementation in Indonesia General Court system, this research used documentary data and analyzed in normative juridical research methods that focused on legal materials which are related to the topic. The results of this research indicate that disability access to justice is not fully applied in Indonesia General Court system, caused by the financial placements and the number of people with disabilities cases. Moreover, the implementing regulation as the guidelines for adjudicating people with disabilities cases (as the step to fulfill justice rights) has not been formed yet. This brings the judicial process of people with disabilities' cases run as is for non-disability people without considering the recommendation from medics, psychologist, or psychiatrist.